A Strategic E-Marketing Plan For Reach Internet Services (MSC) Sdn Bhd ( A Joint -Venture Company Of PCCW-HKT And Telstra Corp.) - Sung, Wong Tien (2002)
The objective of this project was to provide a strategic direction for Reach Internet Services (MSC) Sdn Bhd ( REACH Malaysia). The purpose was also to address the challenges as well as opportunities of deploying broadband telecommunications services, mai